Islam dan Pluralisme : Reinterpretasi Konsep al- Ḥanīfiyyah dan as- Samḥah dalam Hadis Nabi - Mohammad Fattahun Ni’am; Mustikawati Mustikawati (2022)
This study reinterprets the meaning of al-ḥanīfiyyah and as-samḥah so that it has a wider contextualization. The portion of tolerance in Islam tends to be greater in the divine religions, namely Christianity and Judaism or the religion commonly called the Hanif religion which has similar genealogy and teachings. The world or non-celestial religions then experienced animitation and were considered primitive. Negative labeling continues to be intertwined with the dominance of divine religion. This outdated concept certainly needs a new, more universal interpretation, considering that discrimination between religions has become a terrible scourge today. The author in dissecting the hadith which reads